Technical Pitfalls of Signal Truncation in Perfusion MRI of Glioblastoma - Wong, Kelvin K.; Fung, Steve H.; New, Pamela Z.; Wong, Stephen T. C. (Frontiers in Neurology, 2016)
Dynamic susceptibility contrast (DSC) perfusion weighted imaging (PWI) is widely used in clinical settings for the radiological diagnosis of brain tumor. The signal change in brain tissue in gradient echo-based DSC PWI is much higher than in spin echo-based DSC PWI. Due to its exquisite sensitivity, gradient echo-based sequence is the preferred method for imaging of all tumors except those near the base of the skull. However, high sensitivity also comes with a dynamic range problem. It is not unusual for blood volume to increase in gene-mediated cytotoxic immunotherapy treated glioblastoma patients. The increase of fractional blood volume sometimes saturates the MRI signal during first-pass contrast bolus arrival and presents signal truncation artifacts of various degrees in the tumor when a significant amount of blood exists in the image pixels. It presents a hidden challenge in PWI as this signal floor can be either close to noise level or just above and can go no lower. This signal truncation in the signal intensity timecourse is a significant issue that deserves attention in DSC PWI. In this paper, we demonstrate that regional cerebral blood volume and regional cerebral blood flow (rCBF) are underestimated due to signal truncation in DSC perfusion in glioblastoma patients. We propose the use of second-pass tissue residue function in rCBF calculation using least-absolute-deviation deconvolution to avoid the underestimation problem.